Valorization of banana peels waste into biovanillin and optimization of process parameters using submerged fermentation. (September 2021) - Saeed, Shagufta; Ur Rehman Baig, Ubaid; Tayyab, Muhammad; Altaf, Imran; Irfan, Muhammad; Raza, Syed Qasim; Nadeem, Fareeha; Mehmood, Tahir
Abstract: Vanillin is used as an aroma and flavoring agent in the food, beverage, and cosmetic industries. Vanilla planifolia is the major source of natural vanillin with a market price of 1200–4000 per kg. To fulfill the market demand, low price vanillin is synthesized chemically i.e., 15 /kg but European and US legislation considers it unnatural and recommends biosynthesis by fermentation. Ferulic acid is the main and costly precursor for vanillin production. It is naturally present in lignin-enriched agricultural wastes. Therefore, the present study was designed to extract ferulic acid from banana peels and then convert it into biovanillin using Enterobacter hormaechei . Different fermentative parameters like substrate concentration, incubation period, pH, temperature, and agitation speed were optimized via submerged fermentation by varying one factor at a time. From 100 g of banana peels, 60 ± 0.35 mg ferulic acid was extracted and used as a substrate for biovanillin production. The maximum significant (p-value < 0.05) production of biovanillin i.e., 3.8 ± 0.14 g/L was observed by bioconversion of 7 g/L of ferulic acid at 24 h of incubation time, pH 7, 30 °C and agitation speed of 150 rpm. Identification of produced vanillin was done by FTIR and quantification by HPLC method. It was found to be 97% pure in comparison to the standard of Sigma-Aldrich. Hence, the fruit by-product i.e., banana peels served as a useful substrate for the biosynthesis of vanillin. These conditions can be further optimized on a pilot scale to commercialize the product. Highlights: Ferulic acid is naturally present in lignin enriched agricultural wastes. Extraction of ferulic acid from banana peels was done and then converted to biovanillin using Enterobacter hormaechei. Fermentation conditions were optimized via submerged fermentation by varying one factor at a time. Identification of produced vanillin was done by FTIR and was found to be 97% by HPLC method. First study on biovanillin production biotechnologically using banana peels as a ferulic acid source.